2017
DOI: 10.1053/j.ajkd.2016.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Estimated GFR, Albuminuria, and Cognitive Performance: The Maastricht Study

Abstract: In the entire study population, albuminuria was independently associated with lower information processing speed, whereas eGFR was not associated with cognitive performance. However, both were more strongly and extensively associated with cognitive performance in older individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 48 publications
7
56
1
Order By: Relevance
“…We are the first to show that hyperglycemia largely explains diabetes-associated worse cognitive performance, which is in line with the results of a recent study (35) that demonstrated that SAF partially mediates the association of type 2 diabetes with reduced gray matter volume. From a pathophysiological point of view, intracellular hyperglycemia induces mitochondrial overproduction of superoxide (36), which, in turn, activates multiple pathways through which hyperglycemia could exert toxic effects on the brain either directly, by triggering neuronal dysfunction and cell death (37), or indirectly, by inducing microvascular and/or macrovascular changes (26,38,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are the first to show that hyperglycemia largely explains diabetes-associated worse cognitive performance, which is in line with the results of a recent study (35) that demonstrated that SAF partially mediates the association of type 2 diabetes with reduced gray matter volume. From a pathophysiological point of view, intracellular hyperglycemia induces mitochondrial overproduction of superoxide (36), which, in turn, activates multiple pathways through which hyperglycemia could exert toxic effects on the brain either directly, by triggering neuronal dysfunction and cell death (37), or indirectly, by inducing microvascular and/or macrovascular changes (26,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular disease was defined as the presence of albuminuria and/or retinopathy. The presence of albuminuria was based on urinary albumin excretion in preferably two 24-h urine collections (26). Fundus photography of both eyes was performed using an auto fundus camera (AFC-230; Nidek, Gamagori, Japan) to assess the presence of retinopathy.…”
Section: Covariatesmentioning
confidence: 99%
“…In both the cross-sectional Maastricht Study and the longitudinal Rancho Bernardo Study, albuminuria but not GFR was associated with worse cognitive performance, with both of these population-based studies having relatively low prevalence of CKD and including participants with diabetes. 15,28 Several smaller cohorts of CKD stages 3–5 also show poorer performance on tests of executive function. 38,39 Supporting the relationship between CKD markers and worse cognitive functioning, one study of 335 elderly individuals with substantial comorbidity described an independent association of albuminuria with larger white matter disease burden and with worse cognitive performance, particularly in executive function.…”
Section: Discussionmentioning
confidence: 99%
“…10 A third more recent study evaluated data from participants in the Maastricht Study, a population-based cohort in the Netherlands with a low prevalence of CKD, and showed an association between albuminuria and lower information processing speed, particularly among older participants, but no significant association between GFR and cognitive performance. 15 All studies enrolled participants with diabetes.…”
mentioning
confidence: 99%
“…We assessed glucose metabolism status, eGFR, smoking behavior, total-to-HDL cholesterol ratio, triglyceride levels, lipid-modifying medication, office or 24 h average ambulatory systolic blood pressure, antihypertensive medication, waist-to-hip ratio, alcohol consumption and educational level as described previously 26, 35, 36 .…”
Section: Methodsmentioning
confidence: 99%